HUBUNGAN ANTARA PENGALAMAN MEMPEROLEH HUKUMAN FISIK DI MASA ANAK DENGAN PERILAKU AGRESIF PADA REMAJA DI SMKN 02 KOTA BENGKULU - Samidah, Ida; Murwati, Murwati; Mirawati, Mirawati (UNIVED Press, Universitas Dehasen Bengkulu, 2018)
The experience of acquiring the child's physical punishment is the physical abuse of a physical parent that can cause pain as a risk or result of a person's wrongdoing. This experience will affect the physical and psychological side of the child that will cause trauma to the child and the attitude of modeling of the behavior received by the child. Research Objectives Known the relationship between experience of obtaining physical punishment since childhood with aggressive behavior as a teenager in class XI in SMKN 2 Kota Bengkulu. Research Methodology The research design which is used is descriptive analytic method with cross sectional approach that is research to study correlation dynamics between risk factors with effect, by approach, observation or data collection at one time (point time approaches).The results showed that 42 (46.2%) students had aggressive and non-aggressive behaviors of 36 (53.8%), of which 54 (69.2%) students had experience of corporal punishment while 24 (30.8%) Students who did not experience the physical punishment of their parents. The results of the chi-square test show that Ha is accepted, this is indicated by a significant number (p value) = 0.004 <Î¬ = 0.05. So it can be concluded that, there is a relationship between experience of obtaining physical punishment in childhood with aggressive behavior in adolescents at SMK N 02 Kota Bengkulu.